Intercultural Prose and the Image of Culture Shock in Contemporary Czech Literature - Lollok, Marek (Bohemica Olomucensia, 2024)
The paper explores the topic of intercultural prose as a highly productive and differentiated stream of contemporary Czech literature. Their authors draw inspiration mainly from their own biographies, emphasizing various sub-themes in different genre modifications. The common base of these works is some kind of confrontation of different cultures, mostly represented by the subjective perspective of a particular character, staying often "on the verge", taking the role of an observer or outsider. A frequent motif is the phenomenon of culture shock in its various stages and forms, as a natural reaction to encountering another/different/foreign culture. In 2022, several intercultural prose novels were published; in our paper we contextualize and characterize the novels Jsem jejich bůh by Josef Pánek and Jolka by Jana Guljuškina, which we consider to be the most significant in the field.
Keywords: Josef Pánek; Jana Guljuškina; intercultural prose; culture shock; contemporary Czech prose